Relative performance of cluster algorithms and validation indices in maize genome-wide structure patterns - Videla, María Eugenia (2021)
Fil: Videla, María Eugenia. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias. Cátedra de Estadística y Biometría; Argentina.